System for semiautomatic tissue classification based on optical diffractometer for biopolymer structure analysis. - A. A. Skrynnik; V. A. Oganessian; A. G. Jablokov; O. V. Gradov (Морфологія, 2018)
An experimental setup for semiautomatic identifying and classification of histological samples and tissue cultures is proposed using Vainstein-described scheme for 3D electron microscopic image analysis. Phasographic holographic and correlational spectral analysis can be realized on such setups. It’s may be used as the basic source of complementary morphological descriptors or database-assisted identifying criteria. The collimator objective on the laser input chain of above listed scheme (including tunable versions of such optical tracts) may be used without aperture or pinhole chains before the sample stage. Projection transformant method also may be introduced in the stereotypic protocol of identification measurements.